Pembuatan Keramik Dielektrik Dari Sistem (ZnO-TiO2) Pada Suhu Sinter 1450Â°C dan Karakterisitiknya - Firmansyah, Lutfi; Suhandi, Andi; Syarif, Dani Gustaman (MESIN, 2007)
Formation Dielectric Ceramic from (ZnO-TiOJ System at 1450C SinteringTemperature and Their Characteristics, Synthesis of dielectric ceramics from (ZnO-TiOJ system at145&C and their characterization had been carried out. This investigation was done in order to knowthepossibility of the application of the ceramics for dielectric ceramics. The ceramics were produced bymixing powder ofZnO and Ti02 with the concentration in such away so that the concentration ofTiO?larger than thestoichiometric concentration ofZn2Ti04 andbysintering at I450"C. Characterization wascarriedout through XRD, microstructural and electrical analyses. The XRDand microstructure analysesshowed that the (ZnO-TiOJ system ceramics formed Zn2.xTi.x04 solid solution which accompanied bytheformation ofZn vacancy defect. No second phasefound in the ceramics. Lattice constant ofthe Zn2.xTii x04solid solution decreasedfollowing the increase ofthe concentration ofTi02 excess (expressed byx). The Ti02 excess affected the grain size of the Zn2.xTi, x04 ceramics although the effect was notsignificant. At high temperature, the excess of Ti02 increased the dielectric constant and dissipationfactor. The ceramicsproduced in this work had relatively low dielectric constant and loss tangent andgood stability in relation to temperature change, so they can be applied as ceramic substrate andcapasitor dielectric.